2013
DOI: 10.1111/socf.12021
|View full text |Cite
|
Sign up to set email alerts
|

Production Teams and Producing Racial Diversity in Workplace Relationships

Abstract: Production teams have become a dominant form of work organization as labor markets have become increasingly diverse. This transition likely affects coworker networks-possibly undermining entrenched patterns of workplace segregation. Contact theory suggests that teams can foster network diversity when workers cooperate and share values emphasizing mutual respect. Yet variants of conflict theory, including the critical teams literature, contend that the benefits of teamwork may be eroded by associated factors, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…Specifically, coworker cohesion reduces the likelihood of all four outcomes and reaches statistical significance for three of the four. This is, by and large, consistent with prior literature and findings on work group integration, cohesion, and the ameliorative protections it might offer (e.g., Ely 2004;Kalev 2009;Payne et al 2013). Poor supervisory relations, in comparison, intensify vulnerability across each of the four outcomes modeled.…”
Section: Impacts On Discrimination and Sexual Harassmentsupporting
confidence: 87%
See 2 more Smart Citations
“…Specifically, coworker cohesion reduces the likelihood of all four outcomes and reaches statistical significance for three of the four. This is, by and large, consistent with prior literature and findings on work group integration, cohesion, and the ameliorative protections it might offer (e.g., Ely 2004;Kalev 2009;Payne et al 2013). Poor supervisory relations, in comparison, intensify vulnerability across each of the four outcomes modeled.…”
Section: Impacts On Discrimination and Sexual Harassmentsupporting
confidence: 87%
“…Although these do little in the way of mediating observed status vulnerabilities, the consistent effects of vertical and horizontal relations are nevertheless noteworthy and thus should be taken seriously future work. Prior research surrounding intragroup appraisal, networks, and interaction (Melamed and Simpson 2016;Webster and Sobieszek 1974;Webster, Whitmeyer, and Rashotte 2004), work team integration and the potential reduction in biases and group divisions it may afford (e.g., Ely 2004;Kalev 2009;Payne et al 2013), and normative standards, procedural expectations, and behavioral actions of immediate supervisors (e.g., Hodson 2001;Maume et al 2013) would be especially useful starting points, especially if integrated with research on concrete aspects of workplace policy and inequality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefits of teamwork (Ahles and Bosworth, 2004;Marks and O'Connor, 2013) are improved workplace productivity, enhanced overall creativity, reduced response times, expanded decision making (Hartenian, 2003) and increased quality of problem solving (Goltz et al, 2008). On the flip side, research has also identified many challenges to working in teams such as the problems team members have with meeting deadlines (Gevers et al, 2006) and the lack of awareness and sensitivity to diversity that many team members possess (Huffman and Cohen, 2004;DiTomaso et al, 2007;Kalev, 2009;Agrawal, 2012;Payne et al, 2013). However, a benefit of teamwork is that it allows for the further development of interpersonal, leadership, and communication skills.…”
Section: Teamworkmentioning
confidence: 99%
“…Finally, such practices must consider that performance-based compensation is associated with work intensification (Ogbonnaya, Daniels & Nielsen, 2017). On the other hand, studies show that shorter working hours (Kennedy et al, 2013), participative leadership practices (Benoliel & Somech, 2014), and teamwork (Alfes et al, 2018;Payne et al, 2013) can decrease intensification, whereas lack of support by supervisors can increase it (Mauno et al, 2019).…”
Section: Table 2 Number Of Articles and Citations In Major Research A...mentioning
confidence: 99%